Determination of Essence and Practical Mechanism for Conclusion of Forward Agreements (example of PJSC «Agrarian Fund») (Economics and region, 2019)
The concept, essence and analysis of the practical mechanism of activity and performance of forward transactions on an example of PJSC «Agrarian Fund» are analyzed. The concept of «forward transaction» is defined.
Keywords: forward transaction; agrarian market; agrarians; agricultural producer; forward program